THE DESIGN CHARACTERISTICS OF INDONESIAN AND GERMAN HOTEL WEBSITES: A CROSS-CULTURAL COMPARISON - Rora Puspita Sari; Fajar Kusnadi Kusumah Putra (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
The purpose of this paper is to evaluate the Hotels website design of two culturally discrete countries. Indonesian Hotels website represents the eastern countries that have high-context culture, while Germany Hotel websites represent low-context culture. This study evaluates the website of both countries to seek differences in terms of design elements. This study used samples from 60 five stars hotel in Indonesia and Germany. Content analysis was used to evaluate the website design of the hotel in Indonesia and Germany. The Mann-Whitney U test was performed to compare the differences between Indonesia and German hotel website design. The results of this study found that there is a significant difference in hotel website design between Indonesia and the German in terms of website presentation and navigation. Indonesia hotel website also founded to have lower design quality compared to the German hotel website. The results proved that that hotel website from the high-context culture has lower quality than the hotel websites which have a low-context culture. Future research can be conduct by adding more samples to provide better statistical results as well as to add more hotel categories based on the class of hotel